STARBENCH: the D-type expansion of an H II region - Bisbas, Thomas G.; Haworth, T. J.; Williams, R. J. R.; Mackey, J.; Tremblin, P.; Raga, A. C.; Arthur, S. J.; Baczynski, Christian; Dale, J. E.; Frostholm, T.; Geen, S.; Haugbølle, T.; et al. (Monthly notices of the Royal Astronomical Society, 2015)
Abstract. STARBENCHis a project focused on benchmarking and validating different star formation andstellar feedback codes
Gesehen am 26.05.2020